Analysis Of Production Cost For Determining The Selling Price Of Broiler Chickens At Cv Kurnia Agung Babatan - Anisa, Rici; Afriani, Sulisti; Hidayah, Nenden Restu (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the calculation of production cost as a basis for determining the selling price of broiler chickens at CV Kurnia Agung Babatan. The research was conducted using a descriptive quantitative method with a case study approach. Data were collected through observation, interviews, and documentation. The production cost was calculated using the Full Costing method, while the selling price was determined using the Cost Plus Pricing method with a profit margin of 25 percent. The results show that the total production cost incurred during the July–August 2025 period amounted to Rp403,025,155, with an average production cost of Rp22,722 per chicken. Based on the Cost Plus Pricing method, the ideal selling price should be Rp28,402 per chicken, but the actual selling price applied is Rp20,000 per chicken. This indicates that the company has not fully considered all production cost components in determining the selling price.